Implementation Of Critical Incident Stress Management For Atc Work Stress At Jakarta Atc Center - Sitta Annisa; Imam Sonhaji; Rahmawati Sukra (International Journal Of Humanities Education and Social Sciences (IJHESS), 2026)
Aviation safety is a fundamental aspect of the aviation industry, which is characterized by high dynamics and risks. Air Traffic Controllers (ATC) play a crucial role in ensuring the smooth flow of air traffic; therefore, their workload and exposure to critical incidents may generate significant psychological pressure. If left unaddressed, such stress can affect both work performance and mental health. One of the globally recognized strategies to mitigate this issue is Critical Incident Stress Management (CISM). This program consists of pre-incident education, defusing, debriefing, peer support, and long-term psychological follow-up. This study aims to examine the impact of CISM implementation on the work-related stress levels of ATC at Soekarno-Hatta International Airport. The research employed a quantitative method with a causal associative design. Data were collected through Likert-scale questionnaires, interviews, observations, and documentation. The analysis was carried out using multiple linear regression tests to determine the effect of CISM on work stress. The findings are expected to confirm the effectiveness of CISM in enhancing mental resilience, improving decision- making abilities, and preventing psychological disorders. Practically, the study offers recommendations for AirNav Indonesia and airport management to design more structured psychological support policies for ATC personnel